African Swine Fever Vaccine Candidate ASFV-G-ΔI177L/ΔLVR Protects Against Homologous Virulent Challenge and Exhibits Long-Term Maintenance of Antibodies - Sun A Choi; Yeonji Kim; Su Jin Lee; Seong Cheol Moon; Keun Seung Ahn; Xinghua Zheng; Do Soon Kim; Se Young Lee; Seung Pyo Shin; Dongseob Tark; Wonjun Kim; Yongwoo Shin; et al. (Animals)
African swine fever virus (ASFV) has substantially spread worldwide, resulting in significant economic losses in the swine industry. Despite extensive research, no ASF vaccine has surpassed the effectiveness of live attenuated vaccines. For instance, the live attenuated vaccine ASFV-G-ΔI177L/ΔLVR has demonstrated good efficacy and safety, along with prolonged persistence of ASF antibodies after vaccination. Therefore, we aimed to evaluate its potential for protection against highly virulent homologous ASF viruses based on changes in the farm environment. To this end, we challenged domestic pigs with a virulent field strain of ASFV following intramuscular immunization with ASFV-G-ΔI177L/ΔLVR. We further assessed its genomic stability and long-term antibody persistence in immunized domestic pigs. All vaccinated pigs exhibited high antibody positivity, with higher levels of antibodies observed at the time of challenge. These high ASF vaccine antibodies were maintained for approximately 2 months after vaccination. In addition, no organ or tissue damage was observed in the vaccinated animals. Our findings demonstrate the applicability of this vaccine candidate in the prevention of ASFV infection in the swine industry.